Alternative Charges on Private Vehicles as a Way of Managing Urban Mobility - Marins, Cristiano Souza; Dante Filho, Romulo Orrico; Silva, Wellington Nascimento (TeMA - Journal of Land Use, Mobility and Environment, 2014)
In this article, we reflect on proposals for the use of urban tolls on private vehicles as a form of urban mobility management. The methodology used exploratory research for the development of a theoretical basis and a table was drawn up showing the experience in various countries. The conclusion is that toll fees are economic viable, the social and environmental benefits are considerable and this can be considered an important sustainable mobility strategy